Patients' experiences towards the donation of their residual biological samples and the impact of these experiences on the type of consent given for secondary use: A systematic review - Wai, C.; Mackey, S.; Hegney, Desley (University of Adelaide, 2011)
Background: Residual or leftover clinical tissues are valuable resources for biomedical research. There is on-going discussion about the methodological, legal, and ethical issues on the collection, storage and use of these tissues for future research. This systematic review will consider qualitative studies previously conducted, which report on patients' preferences, experiences and willingness to donate their tissues. Objectives: The aim of this review was to critically appraise, synthesize and present the best available evidence related to the experiences of patients toward consent when donating their leftover tissue for research. Search strategy: The search strategy aimed to find both published and unpublished studies. A three-step search strategy was utilized. An initial limited search of MEDLINE and CINAHL was undertaken, followed by analysis of text words contained in the title and abstract, and of the index terms used to describe the article. A second search using all identified keywords and index terms was then undertaken across all included databases. Thirdly, the reference lists of all identified reports and articles were searched for additional studies. Data collection & analysis: The standardised data extraction tool from the Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI-QARI) was used to extract data from each paper. The qualitative research findings were presented as thematic pooling using the JBI-QARI approach in a narrative form. During the analysis, 131 study findings from 18 publications were aggregated into 19 categories to form four synthesized findings.Main results: The synthesized findings generated were: (1) Healthcare professionals should be aware that patients' consent to the use of their left-over tissues are influenced by many and varied factors. Primarily these factors included: benefits to self and other and trust in research and researchers; (2) Healthcare institutions and regulatory authorities must provide strict safeguards and controls in order to maintain privacy and confidentiality of the patients; (3) Healthcare professionals should be aware that the views on ownership and rights to the tissues will vary between individual patients; (4) Healthcare professionals, institutions and regulatory authorities should be aware that patients have different views on the commercial use of their tissues. Discussion: Patients would prefer that institutions requesting donation of leftover tissues establish a good governance system for the collection and storage of tissues, as well as a system for protecting the rights and confidentiality of patients. Most patients prefer to have an ethical and effective system, which decides the future use of their tissues, especially when a full informed consent is not obtained from the patients at time of donation and subsequent use.Implications for Practice: The results from this review can assist researchers and policy makers to understand the experiences of patients and their attitudes and preferences on the collection, storage, distribution and use of their leftover tissue for research. This is especially so when designing a prospective model of consent regimen, to respect patients' needs and make recommendations for the use of existing and previously collected biological samples with no consent taken. Implications for Research: Further qualitative research can be undertaken to ascertain patients' expectations when they donate their tissues; the type of consent model to be used; the perceived risks of genetic and stem cells research; and the effects of culture, religion and age on patients' willingness to donate their leftover tissues for future research.